PENERAPAN E-LEARNING BERBASIS WEB BLOG PADA PEMBELAJARAN BOLA VOLI KELAS X DI SMK PERTANIAN NEGERI 2 TUGUMULYO KABUPATEN MUSI RAWAS TAHUN PELAJARAN 2021/2022 - Risky Darmawan; Dodik Mulyono; Rais Firlando ($$8@@&&$%K, 2021)
This study aims to determine the completeness of the learning outcomes of eighth grade students of SMP Negeri 9 Lubuklinggau after the application of Web Blog-based E Learning learning media significantly. The research method used is quasi-experimental. Data collection techniques in research using tests. The design in this study used a design pattern of Pre-test and Post-test one group design because this design did not use a control class. Based on the results of the study, it can be concluded that after the application of Web-based E-Learning blogs on the football learning outcomes of XI grade students of SMK Negeri 2 Tugumulyo, it was significantly completed. The average student learning outcomes of the experimental class were 80.38, after being analyzed using the formula (z test) it showed that the value was > (6.35 > 1.64) so ​​it could be concluded that H0 was rejected and Ha was accepted. So it can be concluded that the average learning outcomes of Class XI students of SMK Negeri 2 Tugumulyo after implementing Web-based E-Learning blogs are more than or equal to 75. ).